A Nano Approach to Formulate Photosensitizers for Photodynamic Therapy - Pallavi, Pragya; Sharmiladevi, Palani; Haribabu, Viswanathan; Girigoswami, Koyeli; Girigoswami, Agnishwar (Current Nanoscience, 2022)
Conventional treatment modalities for tumors face a variety of pitfalls, including nonspecific interactions leading to multiple adverse effects. These adverse effects are being overcome through innovations that are highly intense and selective delivery of therapeutic agents. More recently, Photodynamic therapy (PDT) has gained its value over conventional chemo- and radiotherapies due to the use of photosensitizers (PS) with an illuminating light source. Photosensitizers have crossed three generations with Photofrin being the first clinically approved PS for PDT. Even though these PS have proved to have cytotoxic effects against tumor cells, they suffer the selective distribution and concentration into the tumor sites that are deeply localized. To overcome these disadvantages, nanoformulations are currently being employed due to their unmatched physicochemical and surface properties. These nanoformulations include the encapsulation of PS acting as a nanocarrier for the PS or the functionalization of PS onto the surface of nanoparticles. The design of such nanoformulations involved in PDT is critical and valuable to consider. Along with PDT, several multifunctional approaches are being uplifted in the current trend where combined therapy and diagnosis are of great importance. Furthermore, targeted, selective, and specific delivery of the PS-loaded nanoformulations with receptor- mediated endocytosis is of interest to achieve better internalization into the tumor site. ROS generation with the interaction of PS augments cell death mechanisms exhibited due to PDT, leading to the immunogenic response that further results in an adaptive immune memory that prevents recurrence of tumor metastasis. Therefore, this review concentrates on the mechanisms of PDT, examples of nanocarriers and nanoparticles that are employed in PDT, combined therapies, and theranostics with PDT. Moreover, molecular mechanisms of nano-based PDT agents in killing tumor sites and designing considerations for better PDT outcomes have been discussed.
Keywords: Nanoformulations